Universal chronicles in the High Middle Ages - Campopiano, Michele; Bainton, Henry (Writing history in the Middle Ages ;, 2017)
Found in pre-modern cultures of every era and across the world, from the ancient Near East to medieval Latin Christendom, the universal chronicle is simultaneously one of the most ubiquitous pre-modern cultural forms and one of the most overlooked. Universal chronicles narrate the history of the whole world from the time of its creation up to the then present day, treating the world's affairs as though they were part of a single organic reality, and uniting various strands of history into a unifed, coherent story. They reveal a great deal about how the societies that produced them understood their world and how historical narrative itself can work to produce that understanding. The essays here offer new perspectives on the genre, from a number of different disciplines, demonstrating their vitality, flexibility and cultural importance, They reveal them to be deeply political texts, which allowed history-writers and their audiences to locate themselves in space, time and in the created universe. Several chapters address the manuscript context, looking at the innovative techniques of compilation, structure and layout that placed them at the cutting edge of medieval book technology. Others analyse the background of universal chronicles, and identify their circulation amongst different social groups; there are also investigations into their literary discourse, patronage, authorship and diffusion.